"LANCANG KUNING ATAWA SITI ZUBAIDAH" KARYA DASRI AL-MUBARY: SEBUAH PENDEKATAN SOSIOLOGI SASTRA - Chrisna Putri Kurniati (Madah: Jurnal Bahasa dan Sastra, 2015)
This study discusses Lancang Kuning atawa Siti Zubaidah by Dasri Al-Mubary. The problem in this research about outlook on life, hierarchical structure, and the condition of cultured patriarchal society in the drama. The purpose of this study is to describe the way of life, a hierarchical structure, and the condition of civilized society patriarchy. The theory used is sociology literature. This is a qualitative study using literature. The primary data is drama Lancang Kuning atawa Siti Zubaidah in a book entitled Obladi Oblada written by Dasri Al-Mubary works published by the Yayasan Sagang, Pekanbaru, 2006, 169 pages thick. The conclusion of this research is that there is harmony human relationship with God and harmony of human relationships with human. Structure hierarchy within the Malay community consists of four layers. The role and position of women in a patriarchal society culture make women can not be separated from domestic work. The existence of stereotypes in society create the assumption  that  the notion of women are as sex objects.